Therapeutic ultrasound associated with essential oils of copaiba and tea tree for healing skin lesions - Mororó, Darrielle Gomes Alves; Albuquerque Brandão, Maria Girlane Sousa; Ponte, Vanessa Aguiar; Silva, Alan Sidney Jacinto da; Batista, Francisco Walyson da Silva; Veras, Vivian Saraiva; Araújo, Thiago Moura de (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: to evaluate the effectiveness of low-frequency ultrasound associated with copaiba and tea tree oil gel in healing skin lesions. Method: quasi-experimental study with pre and post-tests in a single group, carried out in a public hospital in Ceará, Brazil, from March to September 2017, with 14 participants who received 10 treatment sessions. Results: there was an average reduction of more than 20 cm² from the 1st to the 5th application. The reduction in the initial size for the 10th session was over 50%. There was statistical significance (p = 0.0043) between the initial evaluation and the 10th therapy evaluation, with an average reduction of 37 cm². There was a reduction in the intensity of pain reported by the participants and 62.5% were free of pain after applying the therapy. Conclusion: the use of the gel with copaiba and tea tree oil points to an alternative coverage associated with biostimulators such as ultrasound. The composition of the gel oil helped in the application and in the reduction of the maceration of the edge of the wounds, as well as the control of the exudate of the lesion.